O corpo e o material: uma reflexão social do desejo na vida, através da arte - Marco Paulo Ribeiro Rolla (2006)
Looking over Art history and the history of man searching about his desires, I made a parallel between my own art poetics and the actions in these histories, understanding contemporary days as a development of each reality. To relate social situations from nowadays with propositions in my Art work, as we are results of our environment and only with a distant and analytic gazing, we can get a critical vision of life in the present time. When making connections with artists and movements in Art that took my attention over its strong energy of transformation in each reality, I try to analyze similarities and the importance of this actions and people to give us the possibility of today use Art as a tool to reflect life.